A new paradigm of management in the economy of digital and inclusive development - Rakhmanov, A.Q. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2022)
Digitalization plays a key role in ensuring inclusive economic growth and is an important tool in the management system. Currently, the digital economy determines the role of world leaders in the system of global governance, ensuring inclusive growth. The relevance of the study lies in the fact that in the management system it is necessary to form effective organizational, managerial and economic mechanisms for the formation of a digital model inclusive growth. The digital economy sets a new paradigm for the development of not only the state, the economy, but also the entire society. It is a model that can ensure sustainable inclusive growth and help address the accumulated imbalances between countries in the context of globalization.
Keywords: andinclusiveness; digitalization; economy; state; management; investment